2018
DOI: 10.4172/2472-5005.1000130
|View full text |Cite
|
Sign up to set email alerts
|

The Real-Time Comprehension of Idioms by Typical Children, Children with Specific Language Impairment and Children with Autism

Abstract: ObjectiveWe examined on-line auditory idiom comprehension in typically developing (TD) children, children with specific language impairment (SLI), and children with autism. Theories of idiom processing in adults agree on a reliance on lexical/semantic memory for these forms, but differ in their specifics. The Lexical Representation hypothesis claims that literal and non-literal meanings are activated in parallel. The Configuration hypothesis claims that a non-literal meaning will take precedence, such that a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 65 publications
0
12
0
5
Order By: Relevance
“…In general, testing for online performance seems preferable. For instance, Walenski and Love's (2017) priming study on idiom comprehension found that both TD and DLD individuals contrast with ASC subjects in that both TD and DLD groups do not interpret idioms literally. While they predicted that high-functioning (HF), linguistically able, ASC children would perform like typically-developing children, their processing style was quite different compared to the other two groups, including the DLD group, which, on average, had less developed structural language than the ASC group.…”
Section: Linguistic-semantic Abilitymentioning
confidence: 99%
See 3 more Smart Citations
“…In general, testing for online performance seems preferable. For instance, Walenski and Love's (2017) priming study on idiom comprehension found that both TD and DLD individuals contrast with ASC subjects in that both TD and DLD groups do not interpret idioms literally. While they predicted that high-functioning (HF), linguistically able, ASC children would perform like typically-developing children, their processing style was quite different compared to the other two groups, including the DLD group, which, on average, had less developed structural language than the ASC group.…”
Section: Linguistic-semantic Abilitymentioning
confidence: 99%
“…Impairments in such pragmatic reasoning abilities, that is, difficulties with appropriate use and interpretation of language, are considered a hallmark of autism spectrum conditions (ASC) (Tager-Flusberg, Paul & Lord, 2005). In particular, individuals diagnosed with ASC are said to be excessively literalists, in the sense that they tend to prefer literal interpretations of words and utterances, even when speakers have non-literal intentions (Chahboun, Vulchanov, Saldaña, Eshuis & Vulchanova, 2016Vulchanova, Talcott, Vulchanov & Stankova, 2012;Walenski & Love, 2017; see Section 2.4 for discussion of the evidence). 1,2 Recently, however, some studies have suggested that the largely heterogenous population of ASC individuals may not be characterised by global pragmatic impairments (Hochstein, Bale & Barner, 2018), and that many high functioning ASC individuals are able to understand scalar implicatures (Van Tiel & Kissine, 2018) metaphors (Kasirer & Mashal, 2016), and even irony (Glenwright & Agbayewa, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This would explain both why ASD individuals are able to improve over time, as this provides a greater number of reinforcements, and why they perform better with supportive contexts, which may act as an aid to memory. One study suggesting this view was that of Walenski and Love (2017). This study explored online auditory idiom comprehension among three groups of children, one consisting of ASD individuals, one of individuals with specific language impairment (SLI) affecting morphology and syntax, and one control.…”
Section: The Acquisition Of Idioms In Neurodevelopmental Disordersmentioning
confidence: 99%